ASPEK PERLINDUNGAN HUKUM NASABAH KARTU KREDIT BANK DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Totok Tumangkar (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2013)
Credit payment system comes in response to market demands that require payment of a transaction of goods and services to be performed in a practical and safe especially in the case of payment by the number of cash transactions in large quantities. Besides payment with the credit system more acceptable by public the system can reduce the risk of crime, all types of transactions in the Electronic Funds Transfer (EFT) have been applied in the Indonesian banking system and the most commonly used in the community in addition to ATM (Automated Teller Machine) is a credit card. One feature of EFT on one payment system is to use a plastic card (credit card, debit card or by means of an ATM). Problems between customer and bank relating to the use of EFT services specifically in this case is a credit card, it can temporarily resolved by reference to the agreement of both parties, the provisions of the Act - Consumer Protection Act (Law no. 8, 1999), related to the matter, a law is needed - a law specifically governing electronic funds transfers that aim better protect customers' interests by setting standards of security and safety aspects of the product, the consumer protection standards, monitoring standards and settling disputes. To select and obtain a credit card is actually not a difficult thing. issues to be discussed is how the protection of credit card customers in terms of the Act - Act No.. 8 of 1999 on Consumer Protection? Referring to the provisions of Article 1320 and Article 1321 Civil Code, a legal agreement is an agreement made upon agreement of the parties, while the agreement is considered invalid (disabled) if it contains any element of duress, mistakes and fraud. As it relates to the provision of information, businesses must provide correct information, to be honest and real about the product to be sold so that consumers do not feel deceived or cheated. Rights and obligations of the parties in terms of consumer protection related to one another, where the rights of consumers will automatically be mandatory for businesses, and vice versa. Some form of credit card abuse that can occur among other things, credit card theft, credit card fraud, credit card use has expired, recording repetitive transactions by the merchant, errors in shipping and credit card information leak and data confidential credit card.